Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-74760-z
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in working memory capacity moderate effects of post-learning activity on memory consolidation over the long term

Abstract: Similar to sleeping after learning, a brief period of wakeful resting after encoding new information supports memory retention in contrast to task-related cognition. Recent evidence suggests that working memory capacity (WMC) is related to sleep-dependent declarative memory consolidation. We tested whether WMC moderates the effect of a brief period of wakeful resting compared to performing a distractor task subsequent to encoding a word list. Participants encoded and immediately recalled a word list followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In contrast to the present methods, participants in the prior study encoded verbal stimuli intentionally. Given recent demonstrations that the benefits of wakeful rest on retention are moderated by the presence of intermediate retrieval tests [ 51 ], as well as working memory capacity [ 52 ], it is possible that the age-dependent results reported by Martini and colleagues [ 44 ] are driven by factors related to test expectancy and/or working memory maintenance, which would be more likely to occur in the context of intentional, as opposed to incidental encoding. Indeed, older adults might be more conscientious and/or motivated to perform well on the memory task, as compared to younger adults [ 69 , 70 ], but of course, other studies have found that older adults are less likely to initiate effective memory strategies [ 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present methods, participants in the prior study encoded verbal stimuli intentionally. Given recent demonstrations that the benefits of wakeful rest on retention are moderated by the presence of intermediate retrieval tests [ 51 ], as well as working memory capacity [ 52 ], it is possible that the age-dependent results reported by Martini and colleagues [ 44 ] are driven by factors related to test expectancy and/or working memory maintenance, which would be more likely to occur in the context of intentional, as opposed to incidental encoding. Indeed, older adults might be more conscientious and/or motivated to perform well on the memory task, as compared to younger adults [ 69 , 70 ], but of course, other studies have found that older adults are less likely to initiate effective memory strategies [ 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with these alternative interpretations, one recent study demonstrated that long-term (7 day) wakeful rest retention benefits were only observed when retention for the stimuli was also tested on the same day as encoding, but there were no long-term benefits of wakeful rest in the absence of the same-day retrieval test [ 51 ]. Moreover, individuals with high working memory capacity have been shown to exhibit a greater wakeful rest benefit for word retention than individuals with low capacity [ 52 ]. It is at least possible that high working memory individuals might be more likely to generate a test expectancy than low working memory individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural data provide further support for this possibility. Individual differences in working memory, which is closely associated with attentional control 36 38 , have been found to moderate consolidation interference effects, where superior working memory is associated with greater interference from task engagement 39 . This finding was postulated to reflect superior working memory ability resulting in a more focused state of attention, which was detrimental to consolidation.…”
Section: Introductionmentioning
confidence: 99%